Report of the National Seminar Held at Madras (Aug. 17-23, 1962) - Planning Commission (Planning Commission, 1963)
The National Seminar on Public Cooperation in Education (1962) highlighted the critical role of community engagement in advancing elementary and social education across India. It emphasized mobilizing local resources through Panchayati Raj institutions, voluntary organizations, and community committees to support schools, literacy drives, and adult education. Key strategies included mid-day meal programs, vocational training, and targeted enrollment campaigns, particularly for girls and underprivileged children. The seminar underscored the importance of continuous monitoring, fundraising, and resource organization to sustain educational initiatives. Overall, the findings reinforced that systematic public cooperation, coordinated with local governance and civil society, is essential for improving access, quality, and effectiveness in educational development nationwide.
Government of India Planning Commission 1963
Government of India Planning Commission 1963
Keywords: Public Cooperation; Community Participation; Elementary Education; Panchayati Raj Institutions; Literacy Drives; Mid-Day Meal Program; Educational Development; Adult Education; Non-Governmental Organizations; School Improvement Committees